Challenging chains to change : gender equity in agricultural value chain development - Laven, Anne (KIT Publishers, Royal Tropical Institute AmsterdamNL, 2012)
Explains how development organisations and private entrepreneurs have found ways to improve the position of women in value chains - especially small-scale women farmers and primary processors.